(untitled) (Bangladesh Journal of Physics, 2024)
This study focused on synthesizing Mg-doped (0, 2, 4 & 6 mol% Mg) molybdenum oxide (MoO3) with a stable crystal structure using the hydrothermal method. X-ray diffraction (XRD) analysis verified the exclusive presence of the orthorhombic phase, free from any combined phases or contaminants. The Williamson-Hall, Halder-Wagner, and Scherer techniques were employed to assess crystallite dimensions and lattice strains. Microstructural parameters, such as dislocation density and lattice parameters, were calculated. FTIR characterization and vibrational behavior of chemical bonds confirmed α-MoO3 formation. SEM images verified a nanobelt structure with random distribution in both undoped and Mg-doped α-MoO3, and revealed that their lengths and widths ranged from 1.493 to 1.784 m and 157 to 252 nm, respectively. Optical band gaps, determined using UV-visible spectroscopy, ranged from 3.05 to 3.15 eV, decreasing with increased doping. After examination of the SEM and optical properties, we found that factors like shape, size, and crystallinity can influence energy gaps. Employing the energy dispersive X-ray (EDX) method to examine the elemental composition confirmed the presence of oxygen, Mo, and Mg in all doped samples. Our work indicates that Mg-doped α-MoO3 is a cost-effective iso-valent element that could find applications in processes such as water oxidation and various other photochemical activities. Bangladesh Journal of Physics, Vol. 31, Issue 1, pp. 17–41, June 2024